2019
DOI: 10.1038/s41598-019-53840-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and mechanistic research on methane adsorption in anthracite modified by electrochemical treatment using selected electrode materials

Abstract: The strong adsorption capacity of methane in anthracite can seriously affect the methane extraction. Electrochemical treatment is an effective way to weaken the capacity of methane adsorption in coal. Iron, copper, aluminum and graphite as four kinds of electrode materials were selected to modify anthracite by electrochemical treatment. The adsorption of methane in anthracite, before and after modification, was tested under different adsorption pressure. Based on the changes of pore characteristics and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The calculation results of the Δγ of lean coal samples are shown in Figure 2 , which shows that the Δγ increased after methane is adsorbed, while the Δγ decreased after modification, and the decrease in Δγ increased with an increase in potential gradient up to 4 V/cm. Besides, the coal samples from the anode zone ( Figure 2 a) decreased larger than coal samples from the cathode zone ( Figure 2 b) at the same electric potential gradient, and the same results were also found by ref ( 23 ). The pressure and temperature of methane adsorption tests were the same; so, the reduction of coal surface energy can only be caused by electrochemical modification.…”
Section: Resultssupporting
confidence: 85%
“…The calculation results of the Δγ of lean coal samples are shown in Figure 2 , which shows that the Δγ increased after methane is adsorbed, while the Δγ decreased after modification, and the decrease in Δγ increased with an increase in potential gradient up to 4 V/cm. Besides, the coal samples from the anode zone ( Figure 2 a) decreased larger than coal samples from the cathode zone ( Figure 2 b) at the same electric potential gradient, and the same results were also found by ref ( 23 ). The pressure and temperature of methane adsorption tests were the same; so, the reduction of coal surface energy can only be caused by electrochemical modification.…”
Section: Resultssupporting
confidence: 85%
“…It can be observed that the electrical resistivityof the samples first decreased rapidly when the measurement frequency increased from 50 Hz to 5 kHz, then decreased slowly, and finally tended to be stable when the measurement frequency was increased from 5 to 200 kHz. This result is consistent with the research on zinccontaminated soil solidified by cement 30 . The electrical resistivity measurements indicate that the frequency used to measure the electrical resistivity of HWBMs should exceed 5 kHz.…”
Section: Electrical Resistivity Change Of Samples To Investigate Thesupporting
confidence: 93%
“…In recent years, the electrochemical method has been successfully applied to many fields of geotechnical engineering, such as the electrochemical consolidation of weak rock [10][11][12] , the electrochemical desalination of rock or soil [14][15][16][17][18][19][20] , the drainage and consolidation of soil by electro-osmosis [21][22][23][24][25][26][27] , and the acceleration of methane desorption in lump anthracite by the electrochemical treatment [28][29][30] . Meanwhile, the electrochemical treatment was used to accelerate the hydration reaction rate to enhance the strength and deformation characteristics of fly-ash-cemented filling materials 31 .…”
mentioning
confidence: 99%
“…Samples with sizes of 60−80 mesh were used, and the operations met the requirements of the tests. 23 A Nicolet iS5 FTIR instrument produced by Thermo Fisher was used to carry out the FTIR tests. The detection wavenumber range of the device was 400−4000 cm −1 with a solution of 4 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
“…17−19 The other is external field stimulation, including ultrasonic, 20 electric field, 21,22 and electrochemical field stimulation. 23,24 These approaches have achieved some positive results; however, limitations such as complex operations, construction costs, and environmental damage still exist.…”
Section: Introductionmentioning
confidence: 99%